Continuous Non-Invasive Arterial Pressure Assessment during Surgery to Improve Outcome - Stenglova, Alena; Benes, Jan (Frontiers in Medicine, 2017)
Abstract: Blood pressure is one of the most important variables evaluated during almost every medical examination. Most national anesthesiology societies recommend blood pressure monitoring at least once every 5 minutes in anesthetized subjects undergoing surgical procedures. In most cases, blood pressure is monitored non-invasively using oscillometric cuffs. Although the risk of arterial cannulation is not very high, the invasive blood pressure monitoring is usually indicated only in the case of high-risk patients or in complex surgical procedures. However, recent evidence points out that when using intermittent blood pressure monitoring short periods of hypotension may be overlooked. In addition, large datasets have demonstrated that even short periods of low blood pressure (or their cumulative duration) may have a detrimental impact on the development of postoperative outcome including increased risk of acute kidney or myocardial injury development. Recently marketed continuous non-invasive blood pressure monitoring tools may help us to recognize the blood pressure fluctuation without the associated burden of arterial cannulation filling the gap between intermittent non-invasive cuff and continuous invasive arterial pressure. Among others, several novel devices based either on volume clamp/vascular unloading method or on applanation tonometry are nowadays available. Moreover, several near-future smart technologies may lead to better hypotension recognition or even prediction potentially improving our ability to maintain blood pressure stability throughout the anesthesia or surgical procedure. In this review article, novel or emerging technologies of non-invasive continuous blood pressure assessment and their potential to improve postoperative outcome are discussed.